TEACHING TECHNIQUES IN SOLO MENGAJAR - , HIZBI KHALIFADINA P, Dr. Endang Soelistiyowati, M.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nowdays, many education communities in Indonesia. The popular communities are Indonesia Mengajar and Indonesia Berkibar. However, the communities can give inspirations to all young people. The aims of this research are to help the young people if their want to build an education community, for teacher or people who will be a teacher who want to teach children in a community, and for parents who want to teach their son or daughter by own in home. Methods of collecting the data are direct observations in one of Solo Mengajar places, interviews, library research and internet research. The direct observation by observing the teachers while teaching in the classes, and the writer participate in class to teach. Also, the writer interview the staff and volunteers in Solo Mengajar. Based on the research, Solo Mengajar uses three kinds of teaching techniques in class, which are Discussion Technique, Speech or Lecturing Technique and Peer Teaching. There are three things, which are analyzed by the writer in order to know the effectiveness of teaching techniques. First is the studentâs ability in answering their teacherâs question. Second is the studentâs ability to do their task. The last is the studentâs ability to be focused on subject. The data show that the students of Solo Mengajar are good in the ability in answering teacherâs questions in the second test than in first test. In the ability to do their task, students are good to do it. On focusing on subject, in the 2nd grade, there are four of six students who can keep focus on teacher. On the other hand, in 3rd there are three students can keep focus when the learning time is going.From the three things before, it can be concluded that the teaching techniques in Solo Mengajar are effective for their students.